Ultrasound-guided percutaneous radiofrequency ablation combined with anti-PD-1 for the treatment of prostate cancer: an experimental study - Chen, Si; Liu, Ruiqing; Duan, Shaobo; Zhang, Beibei; Wang, Yuzhou; Li, Xiaoxiao; Zhao, Yingying; Li, Zesheng; Zhou, Qi; Zhang, Rui; Zhang, Linlin; Xu, Xiaoxia; et al. (Frontiers in Oncology, 2025)
BackgroundThis study seeks to investigate the potential synergistic effects of combining ultrasound-guided percutaneous radiofrequency ablation with anti-PD-1 therapy on prostate cancer, utilizing animal models.MethodsA mouse model of prostate cancer was established by subcutaneous injection of 1 × 106 Myc-Cap cells on the right side of FVB mice. When the volume of the tumors reached about 400mm3, the mice were randomly divided into four groups and received corresponding intervention treatments. Among them, Group 1 was the blank control group, Group 2 was the simple anti-PD-1 treatment group, Group 3 was the simple radiofrequency ablation group, and Group 4 is the group that received percutaneous radiofrequency ablation combined with anti-PD-1 therapy under ultrasound guidance. The growth of the tumors was observed in mice after treatment in each group, tumor tissues were collected, and the immune status of the mice was analyzed through flow cytometry, immunohistochemistry, immunofluorescence, and other methods.ResultsCompared with other treatment groups, ultrasound-guided percutaneous radiofrequency ablation combined with anti-PD-1 therapy significantly reduced the weight and volume of the tumors, demonstrating more effective tumor suppression. At the same time, combination therapy can promote the aggregation of T-cells within the tumor and increase the proportion of cytotoxic T-cells, increase the proportion of M1 macrophages and iNOS expression, and decrease the proportion of M2 macrophages and Arg expression in the local area of the tumors.ConclusionLocal ablation can improve the therapeutic effect of PD-1 monoclonal antibody. Our preliminary results suggest that ultrasound-guided percutaneous radiofrequency ablation, in combination with anti-PD-1 treatment, produces synergistic effects. These effects may be driven by changes in immune cell populations within the tumor’s immunosuppressive microenvironment.